Consumers' willingness to purchase three alternatives to meat proteins in the United Kingdom, Spain, Brazil and the Dominican Republic. (December 2019) - Gómez-Luciano, Cristino Alberto; de Aguiar, Luis Kluwe; Vriesekoop, Frank; Urbano, Beatriz
Highlights: The most likely alternative to meat was the plant-based proteins. Development of alternatives to meat should focus on the product characteristics. High economic group countries have the greatest readiness to substitute meat proteins. Abstract: One of the current trends in dietary preferences involves the transition to a low- or reduced-meat diet, which is often desirable for health and environmental reasons. This change in dietary preferences requires an in-depth insight into consumers' preferences towards a variety of alternative/non-meat proteins. This study aimed to investigate the consumers' preferences and willingness to purchase three alternative dietary protein sources, namely plant-, cultured meat- and insect-based proteins in four countries with dissimilar economic development status (the United Kingdom, Spain, Brazil and the Dominican Republic). It also aimed to determine which factors would most influence the willingness to purchase. From a total sample of 729 valid respondents, psychographic variables were analysed. The alternative protein deemed the respondents' most preferred willing to purchase was the plant-based type since that option tended to be more widely available in the market. Among the analysed economic groups, the countries classified in the higher economic groups tended to show more readiness to replace traditional meats for the three alternatives. Models suggest that the respondents regarded the alternative characteristics and/or the attributes compared to meat as being the most important factors that influence their willingness to purchase rather than environmental, convenience or healthy buying decisions, or a low level of neophobia. If the perception of healthiness, safety and nutritiousness increases one-unit for the cultured meat in Brazil, the probability of willingness to purchase would increase 86.82%. One-unit stronger belief in Spanish that plant-based are healthy, safe and nutritious higher the probability of willingness to purchase 68.74%. One-unit higher perceive the characteristics of healthiness, safety and nutritional content of the insects-based products would increase 68% the probability of willingness to purchase in the United Kingdom, 72% in Brazil and 58% in the Dominican Republic.